Vous êtes sur la page 1sur 2

# Part 2 (1998): Problem 2 (Mechanics)

a) = (sin n 1 + cos n 3) (1) b) The angular momentum can be computed using the relation Li = Iij j , where Iij is the Inertia tensor. In the case at hand,

## Iij = Diag{I, I, (1 a)I } L = I (sin n 1 + (1 a) cos n 3)

(2) (3)

c) We can compute from L = |L|| | cos . Substituting for L and using (1) and (3), we have = arccos 1 a cos2 (1 a)2 cos2 + sin2 (4)

## d) We are the given the following (useful) information

dL dL = +L dt dt
s b L Since there are no external forces on the body, we must have d dt can derive the Euler equations of motion (for zero external forces):

## (6) (7) (8)

where the dotted quantities denote time derivatives and = 1 n 1 + 2 n 2 + 3 n 3 , Iij = Diag{I1 , I2 , I3 }. Since I2 = I3 = I , (8) yields 3 = 0 3 = 3 (t = 0) = cos . This simplies (6) and (7) to 1

1 + a3 2 = 0 2 a3 1 = 0

(9) (10)

This set of dierential equations can be simplied (keeping in mind that 3 is constant) by dierentiating one and substituting in the other. We obtain 1 + (a cos )2 1 = 0 2 + (a cos )2 2 = 0

(11) (12)

Equations (11) and (12) have oscillatory solutions. In order to completely determine the motion, we need to specify appropriate initial conditions. At t = 0, we have = (sin , 0, cos ). Since (11) and (12) are second order dierential equations, we also need to specify the initial values for the rst derivative of . We can determine these = (0, a 2 cos sin , 0). by substituting into the Euler equations (6), (7), (8). We have Solving the dierential equations (11) and (12) yields = (sin cos(a cos t), sin sin(a cos t), cos ) (13)

The angular frequency of rotation about the symmetry axis, is given by the component of along n 3 . Therefore, b = cos (14)

e) The precession frequency p is the angular velocity component along the (conserved) angular momentum L. Therefore p = L |L| (15)

L can be evaluated in terms of the angle as L = I 2 (1 a cos2 ) We then substitute for using the expression for |L|, which is |L|2 = L2 = I 2 2 (sin2 + (1 a)2 cos2 ) Therefore the answer is I 2 L p = 1a+ (2 a)L I
2

(16)

(17)

(18)